SZ_GERICHTE STK 2019 6 vom 13. August 2019 , grobe Verletzung der Verkehrsregeln (EGV-SZ 2019 A 5.4) - SZ Gerichte (2019)
grobe Verletzung der Verkehrsregeln (EGV-SZ 2019 A 5.4) | Strassenverkehrsrecht